Microstructural features of failure surfaces and low-temperature mechanical properties of Ti-6Al-4V ELI ultra-fine grained alloy - Tabachnikova, E.D.; Podolskiy, A.V.; Smirnov, S.N.; Csach, K.; Miskuf, J.; Saitova, L.R.; Semenova, I.P; Valiev, R.Z.; Bengus, V.Z. (Проблемы прочности, 2008)
Microstructural regularities of failure surfaces and low-temperature mechanical characteristics in quasistatic uniaxial tension and compression have been studied for ultra-fine grained structural states of Ti-6Al-4V ELI alloy processed by equal channel angular pressing. Values of the yield stress and uniform strain at 300, 77, and 4.2 K have been compared for structural states of the Ti-6Al-4V ELI alloy that differ in the average grain size and the morphology of α and β phases. Statistical distributions of dimple sizes on the failure surfaces have been studied for different structural states and temperatures. Исследованы особенности микроструктуры поверхностей излома и низкотемпературные механические свойства сверхмелкозернистого ELI-сплава Ti-6Al-4V, обработанного методом равноканального углового прессования, при квазистатическом одноосном растяжении и сжатии. Проведено сравнение значений предела текучести и однородной деформации, полученных при температурах 300, 77 и 4,2 К для разных структурных состояний ELI-сплава ТІ-6А1-4У с различным средним размером зерна и морфологией α- и β-фаз. Исследовано статистическое распределение размеров ямок на поверхностях излома при различных структурных состояниях и температурах.